1957
DOI: 10.1038/bjc.1957.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Carcinogenic Effect of X-Irradiation with Radioactive Iodine on the Rat's Thyroid

Abstract: RATS injected with 30 ,C radioactive iodine (1131) and kept on methylthiouracil for the succeeding 15 months show adenomatous replacement of the thyroid gland and occasional thyroid carcinomas; unirradiated controls treated with methylthiouracil for 15 months develop a moderate number of adenomas but no carcinomas (Doniach, 1950 and1953). The radiation dose, which is comparable to that used in the treatment of Graves' disease, varies extremely widely within the rat's thyroid gland. The following experiment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1962
1962
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…treatments [2], the use of 131 I has been met with several objections, the most significant of which is the question of oxidative stress and carcinogenicity [3,4]. The damage to the thyroid gland from deposition of radioiodine has often been described in literature [5][6][7].…”
mentioning
confidence: 99%
“…treatments [2], the use of 131 I has been met with several objections, the most significant of which is the question of oxidative stress and carcinogenicity [3,4]. The damage to the thyroid gland from deposition of radioiodine has often been described in literature [5][6][7].…”
mentioning
confidence: 99%
“…Doses of 500 to 2000 rads X-rays to the thyroid have been showin to induce adenomas and carcinomas of the thyroid in rats (Doniach, 1956;Frantz et al, 1957;Lindsay et al, 1961). It is of interest, and pertinent to the analysis of the carcinogenic action of radiation, to assess other biological effects oIn the thyroid of this order of radiation.…”
mentioning
confidence: 99%
“…Lindsay et al [8] found that a higher incidence of thyroid malignancy in rats followed rela tively small doses of 1311. X-irradiation doses of only 10 rads are of significant risk to children [2] but the dose of X-irradiation required for carcinogenesis is much lower than for irradiation by 1311 [9], Doniach [10] has proposed that both ionising irradiation and a non-specific stimulus to thyroid growth are needed to induce thyroid cancer and that the growth stimulus is naturally present in children. The thyroidstimulating immunoglobulins which are widely be lieved to be responsible for the hyperthyroidism of Graves' disease might also provide this stimulus to growth.…”
Section: Discussionmentioning
confidence: 99%